Re-centering Indigenous Knowledge Systems into Contemporary Jazz Bass - de Souza, Stephen Calvin (College of Music, 2023)
This project aims to determine how one can incorporate indigenous music and performance practices into contemporary jazz using the double bass and bass guitar as tools for mediation. It specifically investigates the Southern African and the Middle-Eastern regions via the Indian Ocean connection. This project combines performance and ethnography (Wong 2008) and details the process I went through in the pursuit for musical inclusivity as a South African bassist. Several themes emerged from the research and performance process including: the Western and Eastern divide, historical instruments and traditions of the aforementioned regions, the spiritual side of music that leads to healing, formal and informal education and how we can apply this knowledge. In order to investigate indigenous art forms of these regions, the research utilizes musical analysis and transcription, biographical backgrounds, and interviews of artists. Academic and scholarly writings including books, journal articles and dissertations pertaining to the relevant genres and cultural traditions were also used. In some cases the research includes ethnographic methods such as formal and informal interviews, participant-observation, and one-on-one lessons from master musicians. As a result, five stylistically different compositions were produced and performed in a presentational performance that was videoed for further documentation. The compositions take inspiration from a multitude of genres, instruments and styles. The overall aim was to ethically get as close as possible to the sound and traditional aspects with the understanding that I am not a Middle-Eastern or East-African music scholar. Rather, I am a South African bass player in pursuit of a more culturally inclusive model that goes beyond the established Western paradigm. The results suggest that it is possible to adapt certain instrument sounds and styles to a contemporary instrument. This leads me to believe that this same process could be implemented on other instruments, possibly in other genres. Moreover, I am suggesting this be better incorporated within all music performance streams, and not confined to ethnomusicology or world music studies. I believe that there is room for improvement in education to implement a more localized and culturally inclusive learning experience which helps bring more relevancy to their traditions in a contemporary setting.